PENGARUH UJIAN SOCA TERHADAP PERUBAHAN TINGKAT STRES PSIKIS DAN TEKANAN DARAH PADA MAHASISWA TINGKAT I FK UPN "VETERAN" JAKARTA ANGKATAN 2012 - M. Hanifan Irham F (2013)
Students are a group of people that susceptible to stress. Stress could affect escalation of blood pressure, and if it happens continuously it could become a risk factor for getting a cardiovascular disease. The purpose of this research is to know the influence of SOCA exam towards the changing of psychological stress level and blood pressure of first grade students in medical faculty Pembangunan Nasional "Veteran" Jakarta University 2012. The research methods is using analytic comparative with cross sectional approach. Total sample is 89 people using simple random sampling method. The blood pressure measured one day before the SOCA exam and after the SOCA exam using sphygmomanometer (mercury). Stress score was measured using DASS 42 questionnaire one day before the exam and after the exam. The data was analyzed using frequency table, cross tabulation, Wilcoxon test and Marginal Homogeneity test. The Wilcoxon test result is that there is a meaningful difference between the systolic blood pressure one day before the exam and after the exam (p=0,000), and there is a meaningful difference between the diastole blood pressure one day before the exam and after the exam (p=0,001). In Marginal Homogeneity test there is also a meaningful difference between stress level one day before the exam and after the exam (p=0,001). From this research can be conclude that when someone is in stress condition there will be a change in blood pressure (that activated by the simpatic nerve), and a decreasing stressor could affect in the change of stress level.